Barriers and facilitators to recommended physical activity in lower-limb osteoarthritis: protocol for a qualitative study exploring patients and physiotherapist perspectives using the theoretical domains framework and behaviour change taxonomy - Alison Rushton; Matthew James Willett; Carolyn Greig; David Rogers; Sally Fenton; Joan Duda (BMJ Open)
Introduction Osteoarthritis (OA) is the leading cause of disability and pain in older adults. Although increasing physical activity (PA) can help reduce symptoms, patients with lower-limb OA are less active than the general public. Although physiotherapists commonly deliver PA programmes, they lack knowledge of key barriers and facilitators to adherence to prescribed PA that patients with lower-limb OA experience while attending physiotherapy appointments (treatment period) and after discharge (post-treatment period). This study aims to explore the perspectives of patients with lower-limb OA of barriers and facilitators to adherence to physiotherapy prescribed PA in the treatment and post-treatment time periods to inform the development of intervention underpinned by behaviour change theory.Methods and analysis A qualitative study, based on phenomenology, will purposively recruit patients with lower-limb OA who have had physiotherapy. In-depth semi-structured interviews will be undertaken following discharge from physiotherapy at a single time point. Participants’ perspectives of physiotherapy interventions, including barriers and facilitators to prescribed PA and techniques that they felt optimised adherence to physiotherapist PA prescription will be explored (phase I). The acceptability and feasibility of delivering a physiotherapy intervention incorporating the techniques identified in the semi-structured interviews will then be explored through focus groups conducted with physiotherapists (phase II). Data will be coded following thematic analysis, with barriers and facilitators mapped to the constructs on the theoretical domains framework, and behaviour change techniques identified following definitions from Michie’s V1 taxonomy.Ethics and dissemination Findings from this study will inform development of a physiotherapy intervention underpinned by behaviour change theory aiming to optimise adherence to PA prescription in patients with lower-limb OA during the treatment and post-treatment time periods. This study has ethical approval (IRAS 247904) and results will be disseminated through publications in peer-reviewed journals and presentations at conferences and to study participants.